Experimental and numerical prediction of wear coefficient in non-conformal lubricated rectangular contact using continuum damage mechanics. (27th April 2020) - Samadani, Alireza; Akbarzadeh, Saleh
Abstract: Friction and wear play an important role in the tribological performance of any tribo-system. These two parameters are themselves functions of a variety of different factors such as material properties, surface roughness, applied load, sliding speed, and lubricant properties. In this research, experimental and theoretical investigation on the friction coefficient in line contact is conducted. The theoretical part is based on the load-sharing concept and the friction coefficient is obtained assuming non-Newtonian behaviour for the lubricant. The wear coefficient is then predicted using continuum damage mechanics (CDM) approach in which three times the number of cycles for a wear fragment to form is assumed to be equal to the inverse of the wear coefficient. The experimental part is conducted using a pin-on-disk test rig with disks made from ST37 and pin made of AISI 52100 bearing steel. The geometry of the pin is changed to make sure that a rectangular contact occurs. The predicted values for friction coefficient and wear coefficient are compared to experimentally determined values. It is shown that the presented CDM-based approach has the capability to be used for predicting the behaviour of a tribo-system in the mixed lubrication regime.